The Experiences of Safety Among the Lesbian, Gay, Bisexual, Transgender, Queer, Intersex, and Asexual (LGBTQIA) Students at the University of Witwatersrand, South Africa - Matshepo Maebana; Constance Matshidiso Lelaka (Universitas Pattimura, 2026)
Discrimination, prejudice, and hate crimes against members of the LGBTQIA community remain prevalent. As a minority group, LGBTQIA individuals continue to face numerous challenges, despite university policies that describe the campus environment as inclusive. This study adopted a qualitative research approach, with data collected through face-to-face semi-structured interviews. Purposive sampling was used to select participants, and the data were analysed thematically. The findings reveal that members of the LGBTQIA community experience significant safety concerns and do not perceive the university as LGBTQIA-friendly. Five themes emerged from the analysis: understanding of LGBTQIA terminology, perceptions of safety among LGBTQIA students, concerns regarding safe spaces in university residences, lack of a supportive environment, and the various challenges faced by LGBTQIA students. This study contributes to existing knowledge by providing a foundation for further research, informing and strengthening inclusive interventions and policies, and supporting LGBTQIA advocacy efforts aimed at creating safer environments that promote the well-being and rights of the LGBTQIA community.